Mathematics Learning : Built the Independence of Student using Problem-Based Learning - Reni Dwi Susanti; Marhan Taufik (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
The purpose of this study is to describe how Problem based learning to train student independence. This type of research used a descriptive with a qualitative approach. Data collection techniques using observation and questionnaires. The study was conducted on students who were taking Basic Logic courses, totaling 23 students. Data analysis techniques by data reduction, data presentation, and concluding Problem Based Learning. The results showed that the average implementation of learning with Problem Based Learning was 86.83%, and the learning independence of students from the observations was 62.29% which was included in the good category supported by the results of the questionnaire independence with an average of 70.78% which in the high category. These results indicate that learning by using Problem Based Learning can be used to train student independence. The independence aspect that is emphasized is self-confidence, motivation, have responsibilities, discipline, and initiatives that arise during the learning process. Besides that, by applying the Problem Based Learning, the learning process involves students to take an active part, besides that students are also given more responsibility in the continuity of the learning process and their understanding.